2005
DOI: 10.3758/bf03193636
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture and inhibition (of return): The effect on perceptual sensitivity

Abstract: The present study was designed to determine the spatial distribution of attention in displays in which an irrelevant color singleton was present. The results show that at the location of an irrelevant singleton, there is, first, an increased sensitivity (d′), followed later by a reduced sensitivity. The increased sensitivity implies that, first, the irrelevant singleton captured spatial attention, producing an increased sensory gain for input at the irrelevant distractor location. The later-occurring, reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 30 publications
(76 reference statements)
4
53
0
2
Order By: Relevance
“…The results of Experiment 2 in which we observed RT benefits and no costs further support the conclusion that capture of attention by subliminal cues is truly automatic and stimulus-driven. The trend in finding IOR in Experiment 1 also is consistent with this claim, as some have claimed that IOR is the hallmark of exogenous stimulusdriven capture (Mulckhuse et al, 2007;Theeuwes & Chen, 2005).…”
Section: Discussionsupporting
confidence: 76%
“…The results of Experiment 2 in which we observed RT benefits and no costs further support the conclusion that capture of attention by subliminal cues is truly automatic and stimulus-driven. The trend in finding IOR in Experiment 1 also is consistent with this claim, as some have claimed that IOR is the hallmark of exogenous stimulusdriven capture (Mulckhuse et al, 2007;Theeuwes & Chen, 2005).…”
Section: Discussionsupporting
confidence: 76%
“…Desimone and Gross, 1979), we assume that the spatial distance has a modulating effect on performance: a small distance between the two signals should have a higher impact than a large distance, because it should be more difficult to discriminate between the two signals when they are spatially close together. In accordance with the findings of visual search studies (e.g., Mounts, 2000;Theeuwes and Chen, 2005;Theeuwes et al, 2004), where the impact on performance of a spatially close distracter was higher than of a spatially more distant distracter, we expected a stronger impairment of performance in the presence of a nearby irrelevant patch than of a more distant irrelevant patch.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 77%
“…The impact of task-irrelevant signals on detection performance has already been studied in the context of visual search tasks (e.g., Ester and Awh, 2008;Forster and Lavie, 2008;Hickey et al, 2006;Mounts, 2000;Müller et al, 2008;Theeuwes and Chen, 2005;Theeuwes et al, 2004). The general finding is that taskirrelevant salient objects can in fact deteriorate performance (e.g., discrimination or identification of singletons).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…Previous studies employing this method have demonstrated that location cueing can enhance gains for inputs presented at that location (e.g., Hawkins et al, 1990;Handy et al, 1999) and that attentional capture also results in an increased sensitivity at the location at which the singleton captured attention (Theeuwes & Chen, 2005).…”
mentioning
confidence: 99%